Kualitas Arsitektural Bangunan Fasilitas Pariwisata : Analisis Kuantitatif Pada Data Kualitatif Dengan Menggunakan Metoda Semantic Diffrential - Perpustakaan UGM, i-lib ([Yogyakarta] : Unit Informasi Inovasi Proses Pembelajaran(UI2P2) UGM, 2005)
ABSTRAK Thi research is aimed to find out architectural quality of tourism facilities in the form of built environment (buildings) from the tourist point of view, and architectural composition characteristics of the façade which exist empirically at the buildings within each architectural quality categorization